(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The prime objective of this investigation is to evaluate phytochemical constituent of root, stemand leaves of Cleome viscose by qualitative and quantitative assay. The phytochemical screeningrevealed the presence of alkaloids, cardiac glycosides, flavonoids, phenols, saponins and tannins whichhave tremendous medicinal values.